Maternal vitamin D status in pregnancy is associated with adiposity in the offspring: prospective observational study - Crozier, Sarah R (Am J Clin Nutr, 2012)
OBJECTIVE: To determine the relationship between maternal vitamin D status in pregnancy and body composition in the offspring. DESIGN: Prospective mother-offspring cohort study. SETTING: Southampton, UK. PARTICIPANTS: 977 pregnant women whose serum 25-hydroxyvitamin D concentration (25(OH)D) was measured in late pregnancy and their offspring, followed up within 3 weeks of birth, and at 4 and 6 years of age. MAIN OUTCOME MEASURES: Offspring lean and fat mass assessed using Dual X-ray Absorptiometry. RESULTS: Median daily vitamin D intake (from food and supplements) in late pregnancy was 3.7μg/day (IQR 2.7 to 5.7). 22% of the women took vitamin D supplements in late pregnancy, but only 8.5% of the women complied with UK guidance to take 10μg per day. Median maternal serum 25(OH)D in late pregnancy was 62nmol/l (IQR 43-89); 35% of the women studied had values below 50 nmol/l. Lower vitamin D status was associated with lower fat mass in the offspring at birth, but with greater fat mass at 4 and 6 years. It was not associated with lean mass at any of the ages studied. The opposing associations seen between maternal 25(OH)D (SDs) and fat mass (SDs) in the offspring at birth and at 6 years were robust to adjustment for a range of confounding factors, including maternal BMI and weight gain in pregnancy (β (95% CI) 0.08 (0.02, 0.15) and −0.10 (−0.17, − 0.02 respectively). The key independent predictors of higher maternal vitamin D status were season of measurement and taking vitamin D in dietary supplements in late pregnancy. CONCLUSION: These data suggest that insufficient maternal vitamin D status in pregnancy could result in programmed differences in offspring fat mass. The findings require replication but add to a growing evidence base for a role of vitamin D in the origins of adiposity.